×

# DBMS Inference Rule (IR) MCQs

DBMS Inference Rule (IR) MCQs: This section contains multiple-choice questions and answers on Inference Rule (IR) in DBMS.
Submitted by Anushree Goswami, on April 01, 2022

1. Inference rules are based on ___.

1. Armstrong's Axioms
2. Neilstrong's Axioms
3. Axioms
4. None of the above

Explanation:

Inference rules are based on Armstrong's Axioms.

2. ___ on relational databases can be determined by using Armstrong's axioms.

1. Functional Independencies
2. Functional Dependencies
3. Fractional Independencies
4. Fraction Dependencies

Explanation:

Functional dependencies on relational databases can be determined by using Armstrong's axioms.

3. A type of assertion is the ___ rule.

1. Interference
2. Inference
3. Intraference
4. Indifference

Explanation:

The inference rule is a type of assertion. It can apply to a set of FD(functional dependency) to derive other FD.

4. From the ___ set, we can infer other functional dependencies.

1. Last
2. Middle
3. Initial
4. None

Explanation:

From the initial set, we can infer other functional dependencies.

5. How many types of inference rule are there in functional dependency?

1. 3
2. 4
3. 5
4. 6

Explanation:

There are 6 types of inference rules in functional dependency.

6. Which of the following is a type of inference rule in functional dependency?

1. Reflexive Rule
2. Augmentation Rule
3. Transitive Rule
4. All of the above

Answer: D) All of the above

Explanation:

The types of inference rule in functional dependency are -

1. Reflexive Rule
2. Augmentation Rule
3. Transitive Rule

7. Which of the following is not a type of inference rule in functional dependency?

1. Union Rule
2. Decomposition Rule
3. Pseudo Transitive Rule
4. None of the above

Answer: D) None of the above

Explanation:

The types of inference rules in functional dependencies are -

1. Union Rule
2. Decomposition Rule
3. Pseudo Transitive Rule

8. A determines B if B is a ___ of A in the reflexive rule.

1. Set
2. Superset
3. Subset
4. None

Explanation:

A determines B if B is a subset of A in the reflexive rule.

9. What is the augmentation rule also known as?

1. Partial Independency
2. Total Independency
3. Partial Dependency
4. Total Dependency

Explanation:

Augmentation rule is also known as Partial Dependency.

10. If B is determined by A, then ___ is determined by BC regardless of C in the augmentation rule.

1. AB
2. A
3. B
4. AC

Explanation:

If B is determined by A, then AC is determined by BC regardless of C in the augmentation rule.

11. In the case of Transitive Rule, A determines B, and B determines C if B determines A. Therefore, A must also determine ___.

1. A
2. B
3. C
4. AC

Explanation:

In the case of Transitive Rule, A determines B, and B determines C if B determines A. Therefore, A must also determine C.

12. Union rule states that if A decides B and A decides C, then A must also decide ___.

1. A and C
2. B and C
3. A and B
4. None of the above

Explanation:

Union rule states that if A decides B and A decides C, then A must also decide B and C.

13. What is the Decomposition Rule also known as?

1. Unproject Rule
2. Determined Rule
3. Composite Rule
4. Project Rule

Explanation:

Decomposition Rule is also known as Project Rule.

14. ___ says when A and B are determined by the same process, then A and B are determined separately.

1. Project Rule
2. Decomposition Rule
3. Both A and B
4. None of the above

Answer: C) Both A and B

Explanation:

Decomposition Rule or Project Rule says when A and B are determined by the same process, then A and B are determined separately.

15. If A determines B, and BC determines D, then AC determines D according to the ___ Rule.

1. Transitive Rule
2. Pseudo Rule
3. Pseudo Decomposition Rule
4. Pseudo Transitive Rule

Explanation:

If A determines B, and BC determines D, then AC determines D according to the Pseudo transitive Rule.

16. If A → B and BC → D then ___.

1. AB → D
2. D → AB
3. AC → D
4. D → AC

Explanation:

If A → B and BC → D then AC → D.

17. If A → __ then A → B and A → C.

1. A →C
2. A → AC
3. A → AB
4. A → BC

Explanation:

If A → BC then A → B and A → C.

18. If A → B and A → ___ then A → BC.

1. A
2. B
3. C
4. None

Explanation:

If A → B and A → C then A → BC.

19. If ___ → B and B → C then A → C.

1. A
2. B
3. C
4. None

Explanation:

If A → B and B → C then A → C.

20. If A → B then ___ → BC.

1. AB
2. AC
3. BC
4. None

Explanation:

If A → B then AC → BC.

21. If A ⊇ B then A → ___.

1. NULL
2. 0
3. 1
4. B

Explanation:

If A ⊇ B then A → B.